(untitled) (Research, Society and Development, 2021)
Objective: to understand data about violence against men committed by their intimate partner and its relationship with biopsychosocial impacts. Methodology: The present work is a literature review research, qualitative and descriptive-exploratory, for data analysis, carried out in 2021. Results and Discussion: Studies show that violence against men exists and is becoming a reality increasingly present in the Brazilian and world scenario, with psychological violence being one of the most practiced by their intimate partners. Conclusion: This concludes, emphasizing the importance of this theme and the need for more studies related to it, given the difficulty in finding articles and discussions directed at domestic violence against men, in order to prevent the occurrence of any types of non-violent violence. only against man, but against human beings.